2018
DOI: 10.1103/physrevd.98.081501
|View full text |Cite
|
Sign up to set email alerts
|

Remnant baryon mass in neutron star-black hole mergers: Predictions for binary neutron star mimickers and rapidly spinning black holes

Abstract: Gravitational-wave (GW) and electromagnetic (EM) signals from the merger of a Neutron Star (NS) and a Black Hole (BH) are a highly anticipated discovery. We present a simple formula, validated with 75 simulations, that distinguishes between potential merger outcomes and predicts the baryon mass left outside of the BH after merger. Our formula describes critical unexplored regimes: comparable masses with non-spinning BHs, and higher BH spins, and is essential in assessing whether events such as GW170817 could b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
256
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 233 publications
(262 citation statements)
references
References 59 publications
(55 reference statements)
5
256
1
Order By: Relevance
“…These masses are consis-tent with astrophysical observations of NSs (see e.g. [13][14][15][16]), but it cannot rule out the presence of a stellar-mass BH [17]. Recently, X-ray observations have strongly suggested that the rapidly rotating, giant star 2MASS J05215658+4359220 is the binary companion of a noninteracting ∼ 3M BH [18].…”
Section: Introductionmentioning
confidence: 55%
“…These masses are consis-tent with astrophysical observations of NSs (see e.g. [13][14][15][16]), but it cannot rule out the presence of a stellar-mass BH [17]. Recently, X-ray observations have strongly suggested that the rapidly rotating, giant star 2MASS J05215658+4359220 is the binary companion of a noninteracting ∼ 3M BH [18].…”
Section: Introductionmentioning
confidence: 55%
“…1. Under the assumption that the GW candidate location was covered during the EM observations, we will use a set of three different lightcurve models (Kasen et al 2017;Hotokezaka & Nakar 2019) to predict the proper-2 https://emfollow.docs.ligo.org/userguide/content.html and https://dcc.ligo.org/LIGO-P1900291; Typically, the HasRemnant classification employs the disk mass estimate of Foucart et al (2018) and applies to BHNS systems. BNS configurations are assumed to cause an EM signature, which, as we show later, might not be correct.…”
Section: Introductionmentioning
confidence: 99%
“…The mergers of compact binaries comprised of a neutron star (NS) and stellar-mass black hole (BH) can also eject large quantities of neutron-rich r-process material, provided that the BH is rapidly spinning and of sufficiently low mass to tidally disrupt the NS before the latter plunges inside the BH event horizon (e.g. Foucart et al 2018).…”
Section: Introductionmentioning
confidence: 99%